2012
DOI: 10.1086/663353
|View full text |Cite
|
Sign up to set email alerts
|

No Effect of Carotenoid Supplementation on Phytohemagglutinin Response or Body Condition of Nestling House Wrens

Abstract: Carotenoids are an essential and often limiting resource in animals and play important roles in immune system function. In birds, the period shortly after hatching is an energetically demanding stage characterized by rapid growth in body size and organ systems, including the immune system. Availability of carotenoids for the growing nestlings may be of particular importance and potentially limiting at this stage of development. We tested the hypothesis that the availability of carotenoids for the embryo in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 41 publications
(53 reference statements)
2
5
0
Order By: Relevance
“…Nest effects accounted for over half the phenotypic variation in nestling PHA response, a result consistent with previous studies in this population showing that hatching date and time of injection can influence PHA response of nestling house wrens [ 24 , 25 , 41 , 66 ]. Additional environmental factors might also include food availability, temperature, and parasite load [ 12 ], and we also cannot rule out the possibility of parental effects arising from differential provisioning of broods [ 39 , 55 ] or transgenerational priming of immunity arising from the transfer of maternal antibodies in eggs [ 67 ].…”
Section: Discussionsupporting
confidence: 89%
“…Nest effects accounted for over half the phenotypic variation in nestling PHA response, a result consistent with previous studies in this population showing that hatching date and time of injection can influence PHA response of nestling house wrens [ 24 , 25 , 41 , 66 ]. Additional environmental factors might also include food availability, temperature, and parasite load [ 12 ], and we also cannot rule out the possibility of parental effects arising from differential provisioning of broods [ 39 , 55 ] or transgenerational priming of immunity arising from the transfer of maternal antibodies in eggs [ 67 ].…”
Section: Discussionsupporting
confidence: 89%
“…Contrary to our results, several studies in birds and fish have found a positive effect of dietary carotenoids on the PHA skin swelling immune response (Blount et al 2003;McGraw and Ardia 2003;Aguilera and Amat 2007;Clotfeltera et al 2007;Stirnemann et al 2010), or found that the immune response depletes available carotenoids (McGraw and Ardia 2003;Alonso-Álvarez et al 2004;Aguilera and Amat 2007;Pérez-Rodríguez et al 2008) or found a positive relationship between circulating carotenoid levels and the magnitude of the immune response (McGraw and Ardia 2003;Pérez-Rodríguez et al 2008). However, many other studies of birds and fish show a lack of effects of carotenoid supplementation on the immune response (Navara and Hill 2003;McGraw and Ardia 2005;Biard et al 2006;Hõrak et al 2006Hõrak et al , 2007McGraw and Klasing 2006;Lin et al 2010;Sutherland et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In some growing nestlings bird species, carotenoid supplementation may also increase body condition by regulating oxidative stress resulting from rapid growth (Biard et al 2006), although in other fish and bird species there are no effects (e.g. Pike et al 2010;Sutherland et al 2012), probably because natural food might contain sufficient carotenoids to obscure any benefit of carotenoid supplementation. A similar positive effect of carotenoids on body condition might occur in lizards which have continuous growth and, in our captivity experiment, only have access to some prey types that might not contain enough natural carotenoids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in contrast to findings from similar studies where heritable and/or early maternal effects explained part of the variance in the strength of nestling immune responses to external pathogens (full cross-fostering: Morrison et al 2009; partial cross-fostering: Drobniak et al 2015; but see Saino et al 2008, Rutkowska et al 2012). Investment of anti-oxidants into eggs, such as carotenoids (Berthouly et al 2008, De Neve et al 2008; but see Sutherland et al 2012) and immune factors (Pihlaja et al 2006), have been experimentally demonstrated to influence nestling immunocompetence, we expected a maternal age effect on this trait. Similarly, since nest microclimate and daytime temperature during the brood-rearing period correlate with survival in many species (Monrós et al 2002).…”
Section: Discussionmentioning
confidence: 99%